The Prevalence of Overweight and Obesity Among Children and Adolescents in Mosul City - Alqishawi, Manar A. Y.; Mhmood, Raya H.; Mohammed, Reem I. (Scientific Journal of Medical Research, 2024)
Background and Objective: Childhood obesity represents a growing threat to children’s well-being globally. Growth is faster in middle-income countries and most rapid in lowincome countries and has increased by two to five times during the decades of 1980s, 1990s and 2000 in developed countries. This study aimed to determine the prevalence of overweight and obesity at the level of Mosul city among children and adolescents. Methods: A cross-sectional study was conducted on 6,880 children and adolescents (aged 2–18 years) residing in the city of Mosul between June 2023 and February 2024 to determine the prevalence of overweight and obesity there. Overweight and obesity in children were defined according to the 2007 WHO reference. It is the proportion of children who have a BMI standard deviation score of more than +1 and +2, respectively. It was established how common overweight and obesity were, and statistical comparisons were made between the two growth references, the Center for Disease Control (CDC) and International Obesity Task Force (IOTF), with the World Health Organization (WHO) reference. Results: There were 4581 normal weight children and adolescents from 2 to 18 years of age out of 6880, 58% of whom were boys. Across all age groups, the overall prevalence of obesity and overweight was 11.14 and 11.74%, respectively. The highest percentage of overweight and obesity was in teenage children aged 11 to 15 years, with an almost equal prevalence of overweight and obesity among children in that age group 14.04 and 14.59%, respectively. The overall prevalence of overweight and obesity together (BMI > 85%) according to the WHO was higher, approximately 22.88% (11.14% overweight and 11.74% obesity), than that according to the IOTF and CDC, which was 19.04% (13.99% overweight and 5.05 obesity) for IOTF and was 18.80% (11.45% overweight and 7.35% obesity) for CDC. The prevalence of overweight and obesity is higher among children and adolescents who live on the left side of Mosul city compared to those who live on the right side of the city (25.01 vs. 20.98%). Conclusions: This study showed low to equal levels of overweight and obesity prevalence compared to population groups of other Iraqi cities and low to moderate levels compared to developing and developed countries. Significant associations were found between overweight and obesity with age of adolescence, as well as residence (the right and the left side of town).